PENGARUH INSENTIF TERHADAP KINERJA PEGAWAI BAGIAN KEPEGAWAIAN RUMAH SAKIT UMUM DAERAH KABUPATEN ROKAN HULU - Hasibuan, Verayanti (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Human resourse as aspect that is very infortant in the organizatian to reach sucses full, so to supput the best job need to given to amployert exstra salary to supput ther woking. A cording the writer, the exstra salary that is receaved amployert of RSUD shaow the resourt good. But if it is seen from the amployert of working stell and it have’nts hown the responsible. Based on fenomena a bove, so arice some problems for observation how the appect the exstra salary toward the amployert working of RSUD in regency Rokan Hulu. The result observation and this cussion so the exstra salary have appect that significant to the working amployert in RSUD regency Rokan Hulu. In these, are known from frount counting that is gained the value r (coofition coralition) = 0,89 or 89% it mean, there is realition the exstra salary of amployert and determine coofition is 0,79%, so that linear regrasy method can give contrybution to the working of amployert is 79%, its rest is 21% effeced by the other factors. The counclution is giving the exstra salary is not salary have satefied to the most amployerts in RSUD regency Rokan Hulu.